Modality metaphysics, logic, and epistemology - Hale, Bob 1945-; Hoffmann, Aviv (Oxford Oxford University Press, 2010)
The philosophy of modality investigates necessity and possibility, and related notions--are they objective features of mind-independent reality? If so, are they irreducible, or can modal facts be explained in other terms? This volume presents new work on modality by established leaders in the field and by up-and-coming philosophers. Between them, the papers address fundamental questions concerning realism and anti-realism about modality, the nature and basis of facts about what is possible and what is necessary, the nature of modal knowledge, modal logic and its relations to necessary existence and to counterfactual reasoning. The general introduction locates the individual contributions in the wider context of the contemporary discussion of the metaphysics and epistemology of modality.
Introduction Bob Hale and Aviv Hoffmann -- Metaphysics and logic. Merely possible propositions Robert Stalnaker Response to Robert Stalnaker Aviv Hoffmann Logical necessity Ian Rumfitt Semantic Necessity Kit Fine Modal logic within counterfactual logic Timothy Williamson Is Timothy Williamson a Necessary Existent? David Efird Metaphysical dependence grounding and reduction Gideon Rosen On the source of necessity Ross P. Cameron The reality of modality Anna Sherratt IBE, GMR, and metaphysical projects Scott A. Shalkowski Modal commitments John Divers Response to John Divers Daniel Nolan -- Epistemology. Permission and (so-called epistemic) possibility Stephen Yablo Response to Stephen Yablo David Efird Possible worlds and the necessary a posteriori Frank Jackson Response to Frank Jackson Penelope Mackie Apriorism about modality Scott Sturgeon Response to Scott Sturgeon C. S. Jenkins Conceivability and apparent possibility Dominic Gregory Response to Dominic Gregory Ross P. Cameron.
Includes bibliographical references (pages [347]-257) and index.
Keywords: Modality (Logic).